2022
DOI: 10.1002/rmb2.12488
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the molecular mechanisms of macrophage polarization and metabolic reprogramming in endometriosis: A narrative review

Abstract: Background Endometriosis is an estrogen‐dependent disease and causes pelvic pain and infertility. The limits of current pharmacotherapy in women who desire to become pregnant prompt the development of various targeted molecules for more effective treatment. A review article focused on the unique aspect of cellular metabolic reprogramming of endometriotic cells has been reported. The cellular metabolic pathways are reprogrammed to adapt to a variety of environmental stresses (e.g., nutrient starvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Studies have shown that metabolism can affect the progress of endometriosis. TGF-1 and lactate levels of endometriosis patients are significantly higher than in normal females, and, in particular, the lesions of the disease are highly expressed in glycolytic-related genes, such as HIf1-α, Glut1, Pdk1, and Ldha, as well as the expression of glycolytic related genes; the glycolytic metabolism of the heterotopic endometrium was transferred to the warfarin effect [ 46 , 47 ]. Our study also found that chronic stress alters the microenvironment of endometrium cells and affects their implantation and invasion by affecting multiple metabolic pathways in the lesions of patients with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that metabolism can affect the progress of endometriosis. TGF-1 and lactate levels of endometriosis patients are significantly higher than in normal females, and, in particular, the lesions of the disease are highly expressed in glycolytic-related genes, such as HIf1-α, Glut1, Pdk1, and Ldha, as well as the expression of glycolytic related genes; the glycolytic metabolism of the heterotopic endometrium was transferred to the warfarin effect [ 46 , 47 ]. Our study also found that chronic stress alters the microenvironment of endometrium cells and affects their implantation and invasion by affecting multiple metabolic pathways in the lesions of patients with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…17 It is widely recognized that M1 macrophages are triggered by pathogens, lipopolysaccharide (LPS), interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), and granulocyte macrophage-colony stimulating factor (GM-CSF), whereas M2 macrophages are typically activated by factors, such as interleukin (IL)−4, IL-10, IL-13, transforming growth factor-beta (TGF-β), and immune complexes. 18 Regarding function, M1 macrophages, also known as pro-inflammatory macrophages, can promote inflammation, eliminate pathogenic microorganisms, and combat tumors by secreting various pro-inflammatory factors, such as IL-1β, IL-6, and TNF-α. In contrast, M2 macrophages are anti-inflammatory macrophages that produce a large number of anti-inflammatory factors, such as IL-10, TGF-β, and arginase.…”
Section: The Phenotype and Function Of Macrophage Polarizationmentioning
confidence: 99%
“…Conventionally, naive macrophages (M0) are classified into classically activated macrophage (M1) and the alternatively activated macrophage (M2) based on their function and activation state 17 . It is widely recognized that M1 macrophages are triggered by pathogens, lipopolysaccharide (LPS), interferon‐gamma (IFN‐γ), tumor necrosis factor‐alpha (TNF‐α), and granulocyte macrophage‐colony stimulating factor (GM‐CSF), whereas M2 macrophages are typically activated by factors, such as interleukin (IL)−4, IL‐10, IL‐13, transforming growth factor‐beta (TGF‐β), and immune complexes 18 . Regarding function, M1 macrophages, also known as pro‐inflammatory macrophages, can promote inflammation, eliminate pathogenic microorganisms, and combat tumors by secreting various pro‐inflammatory factors, such as IL‐1β, IL‐6, and TNF‐α.…”
Section: Macrophage Activationmentioning
confidence: 99%
“…Endometriosis is associated with a 50% increase in the risk of epithelial ovarian cancer ( 6 ), and is also correlated with gastrointestinal and immunological diseases and thyroid cancer ( 7 ). Endometriosis is an estrogen-dependent disease, which can be affected by genetics, environmental factors, and the immune system ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%